Ebola fever epidemic 2014: a call for sustainable health and development policies - Fleßa, Steffen; Marx, Michael (The European journal of health economics, 2016)
In 2014 an Ebola epidemic emerged in Western Africa (particularly in Guinea, Liberia, Sierra Leone), which with regard to incidence and prevalence exceeded any previous Ebola epidemic [1]. According to estimates of the World Health Organization more than 26,000 people (including suspected cases) suffered from Ebola until April 2015. About 40 % of them died from this infectious disease [2]. The dynamics and intensity of the epidemic took many experts by surprise. Above all, it represented excessive demands on local health care systems as well as—at least initially—of international organizations tasked with coordinated intervention [3]. From a health economic perspective, especially, the complete dysfunctionality of local health care services is not surprising. The Ebola fever epidemic in Western Africa rather reveals fundamental failures in establishing health policies within those countries as well as in development policies of industrialized nations. In the following, some of these structural defects are outlined and conclusions from the Ebola epidemic are drawn.